Unfurling the Role of Genetic Polymorphism in Rheumatic Heart Disease Pathogenesis - Sharma, Shruti; Chakraborti, Anuradha (Cardiology and Cardiovascular Medicine, 2021)
Rheumatic heart disease (RHD), an autoimmune disease sequel of rheumatic fever, which leads to dysfunction of the heart, is a major public health problem in developing countries that contributes to significant cardiac morbidity and mortality. High mortality was observed in low-income and middle-income countries and even in some groups living in high-income countries. Hence, elucidation of the pathogenic mechanisms in RHD, for therapeutic applications is of major concern and need of the hour. Although, molecular mimicry (MM) is the most established theory for RHD development, however contribution of other factors cannot be ignored. Studies have indicated the role of host-pathogen interacting proteins and immunological factors (T cells-cytokines and chemokines) in RHD, however not much information is available regarding role of polymorphic genes during RHD. The present review, specifically highlights the association of genetic polymorphism with disease manifestation.